Empowering Hands and Voices: Rethinking Technical English in Malaysian TVET - Nor Yazi, Khamis; Azwin Arif, Abdul Rahim; Mohammad Akhmal, Mohamed Supian (UMPSA, 2025)
In the hands-on, high-demand world of Technical and Vocational Education and Training (TVET), students are taught to master the tools of their trade, measuring, welding, calibrating, and repairing. In Malaysia, certificate-level students under the Sijil Kemahiran Malaysia (SKM) programme form the majority of the technical workforce pipeline. These students will become the mechanics, machinists, welders, and technicians of tomorrow. However, amid the grinding of machines and the buzzing of circuits, a quieter yet more pressing issue arises: their struggle to communicate in English, particularly in technical and workplace contexts.